2011
DOI: 10.1115/1.4002348
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Selections for Multicomponent Gas Path Diagnostics Using Analytical Approach and Measurement Subset Concept

Abstract: Gas path analysis (GPA) is a powerful tool to predict gas turbine degradations based on measurement parameters of gas turbine engines. Accordingly, prudent measurement selections are crucial to ensure accurate GPA predictions. This paper is intended to investigate the infiuence of measurement parameter selection toward the effectiveness of GPA algorithm. An analytical methodology for measurement selection, combined with measurement subset concept, is developed to properly select measurements for multiple compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…GT engines are packed with different sensors for different purposes such as process control, health monitoring, and diagnostics. Measurement parameters which are essential for engine performance analysis are known as standard measurements [80]. For instance, these include pressure, temperature, fuel flow rate, and spool speed.…”
Section: Nonlinearity Of the Diagnostic Problem The Relationship Betmentioning
confidence: 99%
See 1 more Smart Citation
“…GT engines are packed with different sensors for different purposes such as process control, health monitoring, and diagnostics. Measurement parameters which are essential for engine performance analysis are known as standard measurements [80]. For instance, these include pressure, temperature, fuel flow rate, and spool speed.…”
Section: Nonlinearity Of the Diagnostic Problem The Relationship Betmentioning
confidence: 99%
“…Larsson [107] developed a systematic design procedure to construct non-linear MB fault diagnosis method for industrial GTs. In another study, Jasmani et al [80], devised a new measurement parameter selection scheme by combining analytical approach and measurement subset concept. Likewise, Chen et al [108] proposed an approach that can select the optimal number of engine measurements for engine GPA purpose.…”
Section: Non-linear Gpa (Nlgpa)mentioning
confidence: 99%
“…Also, Emil Larsson [26] developed a systematic design procedure to construct non-linear model based fault diagnosis method for industrial gas turbines. Jasmani [27], mentioned that effective measurement parameter selection is a very critical issue for GPA based engine diagnostics. To tackle this problem he introduced a new system by combining analytical approach and measurement subset concept.…”
Section: Model Based Diagnostics Methodsmentioning
confidence: 99%
“…Several studies have been reported in the literature where different techniques are used for optimal measurement selection. 22,23 The present measurement subset is considered representative for today's turbofan engines undergoing a pass-off test and hence, will be used as a reference subset in this paper. Table 1(a) and (b) presents a standard set of measured data during pass-off testing.…”
Section: Measurements and Health Indices Selectionmentioning
confidence: 99%